The effect of basic psychological needs on the flow experience in a digital gamified learning setting - Lüking, Sarah; Wünsche, Sarah; Wilde, Matthias (Frontiers in Psychology, 2023)
Digitalization and gamification offer numerous motivation-enhancing opportunities to design biology lessons. For example, digital, gamified learning settings can enhance lessons by offering intense experiences. Such lessons might offer the opportunity to witness flow during the learning activity. For learners, flow can be positively influenced by perceived autonomy, competence, and relatedness. However, previous research on biology lessons has not focused on the impacts of the basic need satisfaction on the flow experience in digital learning settings. To address this research gap, using the topic of the locomotion systems of animals, we investigated students' perceived autonomy, competence, and relatedness as possible predictors of their flow experience while processing a digital, gamified learning environment. The teaching unit was thematically focused on the locomotion system of animals. Our sample consisted of 161 students (46.6% female) from sixth to eighth grade. Students' perceived satisfaction of their basic needs and their flow experience were evaluated. Results confirmed perceived autonomy and perceived competence as predictors of students' flow experience. However, perceived relatedness had no impact on the flow experience. Our findings are in line with the current state of research and prove to be mostly consistent with previous results.